APLIKASI SISTEM PAKAR UNTUK PERLINDUNGAN TANAMAN PADI IR 64 DARI HAMA DAN PENYAKIT - Fixie Vendie Wijayanto; Yudi Wahyu Wibowo; Hendro Joko Prasetyo (Journal of Computer Science and Technology, 2021)
IR 64 is a superior quality rice variety. The advantages are relatively short planting period, strong rice stalks, easy maintenance, fluffier rice and easy to sell because the price is affordable by the community. Pests and diseases are a threat to farmers' rice plants. Various kinds of pest and disease attacks hit farmers' rice plants after the planting season arrived from rats, leafhoppers, tungro and others.Research methodology is a scientific method used to solve a problem. The scientific method means that research activities are carried out using the scientific method so that the method used for data collection and completion is scientifically. With the existence of an expert system for the protection of IR 64 rice plants from pests and diseases, it will make it easier for farmers, agricultural extension workers and ordinary people to protect IR 64 rice plants from pests and diseases and the actions taken to eradicate them without wasting much time, energy and thought.